2019
DOI: 10.3390/nano9060815
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Papers with Tailored Pore Structures Fabricated from Crumpled Graphene Spheres

Abstract: Graphene papers have great potential for various applications, such as electrodes in energy storage devices, protective coating, and desalination, because of their free-standing structure, flexibility, and chemical tunability. The inner structures of the graphene papers can affect their physical properties and device performance. Here, we investigated a way to fabricate graphene papers from crumpled reduced graphene oxide (rGO) spheres. We found that ultrasonication was useful for tailoring the morphology of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Along with this, moving forward toward the real‐time application such as wearable energy devices, the flexibility of the graphene is vital and very recently the porosity combined with the flexible graphene papers or otherwise can be called as paper‐like films, produced from the crumbled rGO through vacuum filtration was reported. [ 27 ] The authors here aligned the porous structure as a separator and the as‐prepared graphene papers as the free‐standing binder‐free electrodes. These materials were elaborately studied for EDLC behavior depending on their sonication time, applied during the vacuum filtration method.…”
Section: Conventional Electrode Materialsmentioning
confidence: 99%
“…Along with this, moving forward toward the real‐time application such as wearable energy devices, the flexibility of the graphene is vital and very recently the porosity combined with the flexible graphene papers or otherwise can be called as paper‐like films, produced from the crumbled rGO through vacuum filtration was reported. [ 27 ] The authors here aligned the porous structure as a separator and the as‐prepared graphene papers as the free‐standing binder‐free electrodes. These materials were elaborately studied for EDLC behavior depending on their sonication time, applied during the vacuum filtration method.…”
Section: Conventional Electrode Materialsmentioning
confidence: 99%
“…Therefore, rather than using additional materials, the surface morphology of the graphene powders was modified to improve dispersion. A simple sonication treatment was used as an effective method to transform crumpled shapes into flat surfaces [ 39 ]. The strong shear stresses and cavitation during sonication treatment altered the crumpled morphology of the graphene powders.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we measured the in-plane electrical conductivity of rGO papers directly fabricated from TGF600 rGO powders without any additional reduction [15]. Owing to the spherical morphology of the TGF600 rGO powders, the paper was formed after sonication treatments which rendered the shapes of the powders flatter and unfolded.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, more sonication treatments enabled the fabrication of rGO papers with more layered stacking and less porosity. In the previous study, an rGO paper fabricated via the sonication of rGO powders for 6 h showed the average electrical conductivity of 152 ± 8 S/m [15]. The density of the rGO paper was estimated to be 0.13 g/cm 3 by using the mass used to fabricate the papers, paper diameter, and paper thickness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation